A biopsychosocial model of fatigue and depression following stroke. Issue 6 (December 2015) - Ormstad, Heidi; Eilertsen, Grethe
Abstract: Poststroke fatigue (PSF) and poststroke depression (PSD) are both common and difficult sequelae following acute ischemic stroke (AIS). Two main perspectives to explain these sequelae are the biomedical perspective and the psychosocial perspective. Research has shown that PSF and PSD are undoubtedly associated with each other, although each can occur in the absence of the other. However, the nature of the relationship is unclear. For example, do stroke patients become fatigued because of being depressed, or do they become depressed because they are fatigued? Alternatively, is there a bidirectional relationship between these two sequelae, with each influencing the other? We propose a biopsychosocial model of PSF and PSD that supports the AIS-induced immune response and kynurenine pathway activation being related to fatigue but not (directly) to depression. We hypothesize that the risk of developing depression may be reduced if the experience of fatigue is acknowledged, and then addressed accordingly.